O67 Preparing for on-call: a new simulation based module for level 6 physiotherapy students. (5th November 2017) - Thackray, Debbie
Abstract : Purpose: Newly qualified physiotherapists are generally expected to participate in respiratory on-call provision, even if respiratory is not their chosen speciality. Graduating physiotherapy students often feel under prepared for this duty, having only had one respiratory placement (ranging from community to acute), with no specific preparation for being on-call. Aims and Objectives: The aim was to prepare physiotherapy students for on-call duties, by developing a level 6 module that used simulation based education (SBE). The underpinning pedagogy used principles from the Integrated Simulation and Technology Enhanced Learning (ISTEL) 1 framework and the conceptual model of cardiorespiratory clinical reasoning. 2 Authentic on-call case studies were modified, and learning outcomes for each case study were mapped to the Association of Chartered Physiotherapists in Respiratory Care (ACPRC) competency matrix. 3 Methods: Students attended eight sessions; six of which were simulations that enabled students to assess and treat real life on-call case studies using simulated patients and a computerised manikin, in an acute ward environment. Students were assessed for competencies with a previously unseen practical simulated on-call scenario, during which they had to assess, treat and communicate their reasoning. This practical assessment was followed with a 1000 word reflective essay about their on-call experience, and a 2, 000-word essay about the evidence base for the treatment they had recommended during the practical scenario. Results: Eighteen students attended the eight sessions of the module and successfully completed the on-call practical assessment. The post module evaluation has been very positive. Students commented that it "was the best change in the curriculum", that "the white elephant had been addressed", and they felt more confident and better prepared. Conclusion(s): This new level 6 module helped physiotherapy students feel better prepared for being on-call when they graduate. Clinicians from the local Trust were involved with facilitating the simulated sessions and their feedback about this new module has also been very positive. The module will be repeated next year and evaluated further. Implications: The instructional alignment of this module was based on a successful post-graduate simulation based education on-call training programme that was implemented at a local Trust in collaboration with clinicians. This new module has followed a similar design principle and so bridges the gap that previously existed between the University and the workplace and gives greater continuity in the development of competency in respiratory care, which ultimately better prepares our students for future clinical practice which may improve patient outcomes. References: . Gough S, Yohannes AM, Murray J. Using video-reflexive ethnography and simulation-based education to explore patient management and error recognition in pre-registration physiotherapy. Advances in Simulation 2016;1(9):1–16. . Thackray D, Roberts LC. Exploring the clinical decision-making used by experienced cardiorespiratory physiotherapists: A mixed method qualitative design of simulation, video recording and think aloud techniques. Nurse Education Today 2017;49:96–105. . Association of Chartered Physiotherapists in Respiratory Care, [ACPRC]. ACPRC Acute respiratory on-call Physiotherapy self-evaluation of competence questionnaire 2007. London: ACPRC.